CASE OF CROHN’S DISEASE IN A CHILD WITH NODULAR PULMONARY TUBERCULOSIS - S. M. Kavtarashvili; S. N. Borzakova; L. A. Kharitonova; V. A. Aksenova; M. S. Scopin (Архивъ внутренней медицины, 2016)
Inflammatory bowel disease (IBD) is an immune-pathological disorder characterized by chronic progressive inflammatory destructive lesion of the gastrointestinal tract. The etiology of the IBD remains unknown. An example of clinical observation is presented to show the difficulty of differential diagnosis between Crohn’s disease and intestinal tuberculosis (TB) in a child with nodular pulmonary TB.